Prevalence of consumption of Empty Calories (ECs) among ECCE attending children in Ringim, Jigawa - Muhammad, Halima Umar; Ibrahim, Baffa Bashari; Abdullahi, Auwalu; Ringim, Iliyasu Ibrahim; Bello, Nafiu (ARKA INSTITUTE, 2025)
Like other beings, children are only able to learn and develop properly if they are consuming healthy foods, instead of unhealthy empty calories, especially at Childhood Care and Education (ECCE) level. Poor dietary experience will surely affect Childhood Care and Education (ECCE) and have a long-lasting effect in the entire life. Childhood Care and Education (ECCE) This study aimed to determine the prevalence of empty calories consumption among Early Childhood Care and Education (ECCE) attending children in Ringim, Jigawa State, Nigeria. A random sampling procedure was used to select 133 participants. Data was collected using a questionnaire and visual observation. Results showed that 57.9% of the children consumed empty calories, with macaroni, spaghetti, and beverages being the most common types. Thus, the implications of this finding is that, the future leaders (children) are exposed to unhealthy foods at schools, which is a risk that is linked to several deadly disorders such as diabetes, cancers, heart disease, hypertension, malnutrition, and so on. Therefore, the future of the society may be at risk. In this vein, all policies makers including the parents should be educated (informed) about dangers of empty calories to children and means to scuttle escalation of the problem. Indeed, the study highlights the need for nutrition education and interventions to promote healthy eating habits among ECCE attending child.